Production, consumption, and quality attributes of Lanhouin, a ﬁsh-based condiment from West Africa - Kindossi, Janvier Mêlégnonfan; Anihouvi, Victor B.; VIEIRA-DALODE, Générose; AKISSOE, H. NOËL; JACOBS, A.; DLAMINI, N.; Pallet, Dominique; HOUNHOUIGAN, DJIDJOHO JOSEPH (My University, 2012)
Indigenous knowledge related to Lanhouin processing, commercialization, and consumption was investigated through a survey in the Mono District in the south of Benin using a questionnaire. The questionnaire focused on the socio-cultural profile of actors, the raw materials used for the processing, the technologies used, the quality attributes, the forms of consumption, and the storage of the product. The data collected were analysed by means of descriptive statistics and correspondence analysis. The results showed that Lanhouin is generally processed in informal small-scale plants. A large number of women are engaged in the production and the trade of Lanhouin and this constitutes the main source of income for most of them. Three variants of technologies were used to produce Lanhouin, but all apparently concluded in the same end product. The appreciation of the quality of Lanhouin by the actors is mainly based on sensory attributes such as the colour, texture, aroma, consistency of flesh, and the general appearance of the product. In Benin, Lanhouin serves various markets: domestic markets and sub-regional markets that contribute to an expanding market. As regards the forms of consumption, Lanhouin is used as a taste and flavour enhancing condiment in some main dishes such as vegetable, slimy vegetable, and tomato sauces.
Keywords: Lanhouin; fermentation; processing; storage; quality; commercialization; consumption